Determinantes sociales y familiares que influyen en el embarazo adolescente de 1ero a 3ero de bachillerato en la Unidad Educativa 23 de junio del Cantón Baba período junio- noviembre 2022. - Briones Contreras, Yamileth Matilde (2022)
Adolescent pregnancy occurs when young people practice sexual activities without ignorance, with irresponsibility and misuse of contraceptive methods, also due to their immature age they are carried away by their desires, which generates problems and consequences in the future. General objective: to analyze the social and family determinants that influence adolescent pregnancies in the June 23 educational unit of the Baba canton. Methodology: the deductive and inductive method was used, a logical historical method applying a quantitative approach, being a descriptive, basic, field and cross-sectional investigation. Data collection: the survey was used through a questionnaire of organized and structured questions. Results: the data analysis was carried out through the Microsoft Excel program where it was observed that the main determinants that influence teenage pregnancies of the June 23 educational unit of Baba canton. Conclusion: when performing the analysis, statistically significant results were obtained that allowed us to accept the study hypothesis where the degree of knowledge and the lack of effective communication within the family nucleus would be the cause of the teenage pregnancies that occurred in the educational unit June 23, Baba canton during the period June - November 2022.